The Crossing of ingo - Dunmore, Helen, 1952- (London : HarperCollins, 2012)
Sapphire, Conor and their Mer friends Faro and Elvira are ready to make the Crossing of Ingo - a long and dangerous journey that only the strongest young Mer are called upon to make. No human being has ever attempted this thrilling voyage to the bottom of the world. Ervys, his followers and new recruits, the sharks, are determined that Sapphire and Conor must be stopped - dead or alive.
5.0
5-8.
5-8
Keywords: Mermaids -- Fiction; Mermen -- Fiction; Mermaids and mermen -- Fiction; Cornwall (England : County) -- Fiction; England -- Fiction; Cornwall (England : County) -- Fiction; England -- Fiction